A Study of Woman Reservation in Political & Constitutional Bodies in India: Examining the Progress of Women's Reservation in Political and Constitutional Bodies (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In the most recent decade of the twentieth century, the issue of political strengthening of ladies picked up energy all through the world. In 1990, the United Nation's Economic and Social Council embraced an objective of 30 for each penny ladies in basic leadership positions on the planet by 1995.